An Investigation of Communicative Interactions and Identities in an EFL Classroom: A Case Study in Southeastern Turkey - Babayiğit, Mehmet Veysi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In communicative settings, participants engage in some kinds of small interactive manners in natural classroom context, and they indicate their language learning potential via multimodal aspects such as using hand movements, gestures, mimics, eye contact, etc. The current study examines the interactions of learners of English as a foreign language (EFL) in natural classroom contexts to investigate how their learner identities reflect in their multimodal interactions. The study is comprised of two cycles; the piloting cycle which lasted three weeks with twenty-six participants, and the main cycle which lasted seven weeks with sixteen participants. The general data collection tools for both cycles are video-audio recordings and interviews (Stimulated Recall Interviews- SRIs). During the data collection period, the participants were asked to participate interactively in the classroom discussions every week around the topics that were previously selected by the researcher. Each of these sessions were video recorded; then the transcripts of them were prepared and analyzed qualitatively based on the conversation and multimodal conversation analyses. SRIs were conducted each week during data collection process in order to provide a chance for participants to view their interactions during the conversations in both piloting and main cycles. The results revealed that the participants were able to develop and indicate some kinds of learner identities such as turn-taking learner identity (which can also be attributed to their knowing learner identity, and social learner identity), unknowing learner identity silent learner identity, and cultural identity. One of the most common observation throughout the study was the participants ‗teacher-dependent learner‟ identity. This can be interpreted as an urgent necessity for teachers to develop themselves professionally so that they would know how to transform their teaching pedagogy into a more effective and learner centred one. It is believed that the findings of this study offer some useful suggestions for further studies which would employ Conversation Analysis (CA) and Multimodal Conversation Analysis (MCA) to investigate other aspects of interactions in EFL contexts under different lenses. Keywords: conversation analysis, multimodal conversation analysis, interaction, identity.

ÖZ: Doğal sınıf ortamlarında yabancı dil olarak Ġngilizce öğrenen öğrenciler iletişim amaçlı etkinliklerde bazı küçük etkileşimli davranışlar içinde olurlar ve konuşmalarını el hareketleri, jestler, mimikler, göz teması vb. sözel olmayan biçimlerde desteklerler. Bu çalışmada, yabancı dil olarak Ġngilizce öğrenenlerinin sınıf bağlamındaki etkileşimleri çok modlu konuşma analizi yöntemiyle incelenerek ‗öğrenen kimliklerinin‘ nasıl geliştiği araştırılmıştır. Çalışma, yirmi altı katılımcıyla üç hafta süren pilot aşama ve on altı katılımcıyla yedi hafta süren ana çalışma aşamaları olmak üzere iki aşamadan oluşmaktadır. Her iki aşama için genel veri toplama araçları, video-ses kayıtları ve uyarılmış geri çağırma mülakatlarıdır. Veri toplama sürecinde katılımcılardan, araştırmacı tarafından önceden belirlenen ve sosyal/kültürel içerikli konular hakkında düzenlenen sınıf içi tartışmalara interaktif olarak katılmaları istenmiştir. Bu oturumların her biri video kaydına alınmıştır. Daha sonra kayıtların transkriptleri çıkarılmış ve bu transkriptler Konuşma Analizi ve Çok Modlu Konuşma Analiz yöntemlerine dayanarak analiz edilmiştir. Video kaydı oluşturulan her sınıf-içi tartışma etkinliğini takip eden haftada, katılımcılara bir önceki haftadaki performanslarından parçalar izlettirilmiş, o anki performansları hakkında sorular sorularak mülakatlar gerçekleştirilmiştir. Bu şekilde toplanan verilerin analiz edilmesi sonucunda ortaya çıkan bulgular, tartışma için seçilmiş olan konuların hemen hemen tüm katılımcılar tarafından ilgi çekici bulunduğu, dolayısıyla konuşma motivasyonlarını artırdığı yönündedir. Ne var ki bazı katılımcılar oldukça utangaç olduklarından dolayı sessiz kalmayı tercih etmiş ve sınıf-içi tartışma seanslarına aktif olarak katılmamışlardır. Sonuçlar, katılımcıların konuşma sırası talep eden öğrenci kimliği (bilen öğrenci kimliğine ve sosyal öğrenci kimliğine atfedilebilir), bilmeyen öğrenci kimliği, sessiz öğrenci kimliği, kültürel kimlik gibi bazı öğrenci kimliklerini geliştirebildiklerini ve gösterebildiklerini ortaya koydu. Çalışma boyunca en yaygın gözlemlerden biri, katılımcıların öğretmene bağımlı öğrenci kimliğiydi. Bu, öğretmenlerin öğretim pedagojilerini daha etkili ve öğrenci merkezli bir pedagojiye nasıl dönüştüreceklerini bilmeleri için kendilerini profesyonel olarak geliştirmeleri için acil bir gereklilik olarak yorumlanabilir. Bu çalışmanın bulgularının, yabancı dil olarak Ġngilizce öğrenen öğrencilerin etkileşimlerinin diğer yönlerini farklı mercekler altında araştırmak için Konuşma Analizi (CA) ve Multimodal Konuşma Analizi (MCA) kullanacak olan çalışmalara bazı yararlı öneriler sunduğuna inanılmaktadır. Anahtar Kelimeler: konuşma analizi, çok modlu konuşma analizi, etkileşim, kimlik.
Doctor of Philosophy in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2021. Supervisor: Prof. Dr. Ülker Vancı Osam.
Keywords: English Language Teaching (ELT); English Language--Study and Teaching--Turkey; Conversation analysis; multimodal conversation analysis; interaction; identity